Optimalisasi Tata Kelola Badan Usaha Milik Desa (BUMDes) di Desa Polohungo Kecamatan Dulupi Kabupaten Boalemo - Nuralim Pasisingi; La Nane; Wila Rumina Nento (Damhil: Jurnal Pengabdian kepada Masyarakat, 2023)
Polohungo Village is a village located in Dulupi District, Boalemo Regency. Polohungo Village Owned by the Village Enterprise (BUMDes) which is used as an alternative in developing the village's potential in increasing community income. However, in the management of BUMDes in Polohungo Village it was found that the objectives in establishing the BUMDes had not been fulfilled, because the community's income and contributions did not match the expected goals. Therefore, it is necessary to optimize BUMDes governance in Polohungo Village. Community service activities were carried out in Polohungo Village, Dulupi District, Boalemo for 45 days, starting from October 4th to November 18th 2022. The training was carried out by providing socialization and training on BUMDes governance.